2014
DOI: 10.4103/0973-1482.136583
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the trough plasma imatinib level monitoring at two time points in patients with the chronic myeloid leukemia-chronic phase

Abstract: Plasma imatinib levels may be of benefit in patients not achieving desired response at defined time intervals. The plasma level monitoring also helps in the assessment of drug compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Twenty studies were included for further analysis based on this search. 1-20 A special issue of the Indian Journal of Medical and Pediatric Oncology reported on the outcomes of CML in Indian centers; all these articles were separately reviewed using the same criteria, and an additional 13 papers were included. 21-33 The references of all publications were reviewed, and an additional four studies were identified and included.…”
Section: Methodsmentioning
confidence: 99%
“…Twenty studies were included for further analysis based on this search. 1-20 A special issue of the Indian Journal of Medical and Pediatric Oncology reported on the outcomes of CML in Indian centers; all these articles were separately reviewed using the same criteria, and an additional 13 papers were included. 21-33 The references of all publications were reviewed, and an additional four studies were identified and included.…”
Section: Methodsmentioning
confidence: 99%
“…A lot of novel agents which can override BCR-ABL1 KD mutations including T315I are being developed but their prohibitive cost remain limiting factor [33]. Measuring plasma imatinib level has been suggested as tool for drug compliance assessment [34]. Molecular monitoring for BCR-ABL1 along with ABL1 kinase domain mutational analysis before administering second generation or third generation TKIs help in better management of patients harboring these mutations.…”
Section: Discussionmentioning
confidence: 99%